2012
DOI: 10.1021/cm3013039
|View full text |Cite
|
Sign up to set email alerts
|

RbBiNb2O7: A New Lead-Free High-Tc Ferroelectric

Abstract: RbBiNb2O7 ceramic is synthesized by solid state reaction of stoichiometric quantities of Rb2CO3, Bi2O3, and Nb2O5 (1000 °C, 24 h) and characterized by powder XRD, Raman scattering spectroscopy, and electrical measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 36 publications
2
42
3
Order By: Relevance
“…In this sense, ferroelectricity in a Dion-Jacobson compound can be explained easily by hybrid improper ferroelectricity. More recently, Li et al reported the experimental realization of high-T c ferroelectric behavior of a RbBiNb 2 O 7 bulk material [32]. The ferroelectric transition temperature of 945°C was confirmed by temperature dependent dielectric constant experiments, Raman experiments, and piezoelectric constant experiments.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In this sense, ferroelectricity in a Dion-Jacobson compound can be explained easily by hybrid improper ferroelectricity. More recently, Li et al reported the experimental realization of high-T c ferroelectric behavior of a RbBiNb 2 O 7 bulk material [32]. The ferroelectric transition temperature of 945°C was confirmed by temperature dependent dielectric constant experiments, Raman experiments, and piezoelectric constant experiments.…”
mentioning
confidence: 93%
“…The spontaneous polarization of the Bi and Nd compound was 35.72 μC/cm 2 and 24.53 μC/cm 2 , respectively. Note that the experimental spontaneous polarization value of the Bi compound with a polycrystalline form was approximately 10 μC/cm 2 [32]. In terms of the tilting angle (shown in Table I), the c + tilting angle for the Bi compound was similar to that of the Nd compound (10.99 vs 10.72), whereas the a − tilting angle for the Bi compound was smaller than that of the Nd compound (5.98 vs 7.25).…”
mentioning
confidence: 99%
“…Actually, [110] polarization widely exists in many perovskite related layered compounds as ground state, such as Aurivillius phase SrBi 2 Ta 2 O 9 , 34 RP phase SrO(SrTiO 3 ) n , 21 and DionÀJacobson type RbBiNb 2 O 7 . 35 The total energy of Aba2 phase decreases with substrate lattice constant, because that compressive strain favors octahedral rotations, as shown in Fig. S4.…”
Section: B Sn 2 Tio 4 Under Strainmentioning
confidence: 94%
“…The concept of HIFs has been typically applied by theorists to mean the imposition of a stable polar ground state in a crystal via the coupling of two or more intrinsically non-polar modes with a polar mode ("tri-linear coupling"), with no requirement for an experimentally-realized polarization reversal. However, such experimental demonstrations of polarization-field hysteresis have now been reported, for example in the Ruddlesden-Popper (RP) phase Ca 3 Ti 2 O 7 [8] and the Dion-Jacobson (DJ) phase RbBiNb 2 O 7 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the recent flurry of work from the theoretical standpoint, it was known that ferroelectricity, or at least polarity, co-existed with octahedral tilting in several layered perovskites, the most well-established being the Aurivillius family, exemplified by SrBi 2 Ta 2 O 9 and Bi 4 Ti 3 O 12 [10]. Snedden et al [11] later made the intuitive link between the nature of octahedral tilting in the DJ phase CsBiNb 2 O 7 and that in SrBi 2 Ta 2 O 9 ; both have a tilt system analogous to that described by the Glazer notation a − a − c + in ABX 3 perovskites.…”
Section: Introductionmentioning
confidence: 99%